African-Born Status and Risk of Hepatocellular Carcinoma among Patients with Chronic Hepatitis B Infection. (4th October 2017) - Kennedy, Kaitlyn; Arora, Nayan; Graham, Susan; Nina Kim, H.
Abstract: Background: Risk factors for hepatocellular carcinoma (HCC) have not been well documented among immigrants to the USA with chronic hepatitis B virus (HBV) infection. All African-born patients are considered high risk for HCC and therefore screened at a younger age, but most data come from West African studies. We conducted a case–control study to identify risk factors associated with HCC among Asian and African immigrant patients with chronic HBV in an academic urban hospital setting in the US. Methods: We identified a total of 278 patients with HCC and chronic HBV seen at two medical centers in a 12-year span from January 2002 to December 2015. These cases were age- and sex-matched in a 1:3 ratio with 823 non-cancer control subjects with chronic HBV. Logistic regression analyses were used to estimate the odds of HCC for each race, with black race stratified by foreign-born status, after adjustment for other demographics and clinical conditions. Results: Of the 278 HCC cases, 67% were 60 years of age or older, 78% were male and 72% were Asian. Twenty percent of 823 HBV controls were black but only 7% of 278 HCC cases were black, of whom 14 were African immigrants (1 each from Chad, Liberia and Senegal and 11 from East Africa: Ethiopia n = 4, Somalia n = 4, Eritrea n = 1, Sudan n = 1, Kenya n = 1). In multivariable analysis, Asian race and cirrhosis were associated with greater odds of HCC (adjusted odds ratio [aOR] 3.2, 95% confidence interval [CI] 2.1–5.1 for Asians and aOR 18, 95% CI 12–27 for cirrhosis). Black race was not associated with HCC: aOR was 1.3 (95% CI 0.6–2.9) for African immigrants and 0.6 (95% CI 0.2–1.8) for non-immigrant blacks. We found no association with HCC and other risk factors including diabetes, HCV coinfection, and HIV coinfection. Alcohol use was associated with HCC but risk appeared to be mediated through cirrhosis as it was no longer associated when cirrhosis was included in the model. Conclusion: Asian patients were the only racial subgroup associated with an increased odds of HCC in our cohort. African-immigrant status was not associated with increased risk of HCC in our mostly East African cohort, suggesting regional differences in HCC risk. Optimal screening strategies for HCC in African immigrants with chronic HBV warrant further study. Disclosures: All authors: No reported disclosures.